The Classical Economists and the Factory Acts–A Re-Examination - Blaug, Mark (Quarterly Journal of Economics, 1958)
I. Introduction: The need for a reconsideration, 211. — II. The first phase of the debate, 1819–1844, 212. — III. The second phase: the Ten Hours Bill, 217. — IV. Mill's disciples and Jevons, 221. — V. Evaluation of the classical analysis, 223.